Cannabinoid Receptor 2 Agonism is Capable of Preventing Lipopolysaccharide Induced Decreases of Cochlear Microcirculation – A Potential Approach for Inner Ear Pathologies. Issue 9 (October 2021) - Weiss, Bernhard G.; Freytag, Saskia; Kloos, Benedikt; Haubner, Frank; Sharaf, Kariem; Spiegel, Jennifer Lee; Canis, Martin; Ihler, Friedrich; Bertlich, Mattis
Abstract : Hypothesis: The ability of JWH-133, an agonist at the cannabinoid receptor 2, to abrogate the effects of lipopolysaccharide on cochlear microcirculation was investigated. Background: Cochlear inflammation and subsequent impairment of microcirculation is part of numerous pathologies affecting inner ear function, including suppurative labyrinthitis, noise trauma, and sudden sensorineural hearing loss. One way of causing cochlear inflammation is exposing the cochlea to lipopolysaccharide, a bacterial endotoxin. Methods: Twenty Dunkin-hartley guinea pigs were divided into four groups of five animals each. Two groups received topic treatment with JWH-133 and two received treatment with placebo. One group that had been treated with JWH-133 and one with placebo were then exposed to lipopolysaccharide or placebo, respectively. Cochlear microcirculation was quantified before, in between and after treatments by in vivo fluorescence microscopy. Results: Significantly different changes in cochlear blood flow were only seen in the group that was treated with placebo and subsequently lipopolysaccharide. Every other group showed no significant change in cochlear blood flow. Conclusion: JWH-133 is capable of abrogating the effects of lipopolysaccharide on cochlear microcirculation. It may therefore be clinical interest in treating numerous inflammation associated cochlear pathologies.